Lepeophtheirus cuneifer Kabata, 1974 (Copepoda: Caligidae) from seawater-reared rainbow trout, Oncorhynchus mykiss , and Atlantic salmon, Salmo salar , in the Strait of Georgia, British Columbia, Canada - Johnson, S. C.; Albright, L. J. (Canadian Journal of Zoology, 1991)
Adults, preadults, and chalimus larvae of Lepeophtheirus cuneifer were recovered from rainbow trout, Oncorhynchus mykiss, and Atlantic salmon, Salmo salar, cultured in seawater in the southern Strait of Georgia, British Columbia. This species has not been reported previously from these hosts or in Canadian waters. It was found only in low abundance and is not an economically important parasite of farmed salmonids in British Columbia.